2021
DOI: 10.1016/j.freeradbiomed.2020.12.438
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming: A driver of cigarette smoke-induced inflammatory lung diseases

Abstract: Cigarette smoking is a well-known risk factor for pulmonary diseases, including chronic obstructive pulmonary disease (COPD), asthma and pulmonary fibrosis. Despite major progress in dissecting the mechanisms associated with disease development and progression, findings only represent one aspect of multifaceted disease. A crucial consequence of this approach is that many therapeutic treatments often fail to improve or reverse the disease state as other conditions and variables are insufficiently considered. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 98 publications
(167 reference statements)
1
11
0
Order By: Relevance
“…Recent evidence suggests that tobacco smoke could lead to metabolic reprogramming 35 . For example, proteomic studies of lung epithelial cells exposed to cigarette smoke revealed an abnormality in oxidative phosphorylation and altered abundance of various enzymes of the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that tobacco smoke could lead to metabolic reprogramming 35 . For example, proteomic studies of lung epithelial cells exposed to cigarette smoke revealed an abnormality in oxidative phosphorylation and altered abundance of various enzymes of the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…At a systemic level, CS exposure has been linked to various metabolic syndromes, such as insulin resistance and abnormal lipoprotein metabolism [81]. At cellular level, CS is known to induce the dysregulation of several metabolic pathways [82]. Thus, CS exposure can not only cause microglia activation but likely keep them locked in an activated state, which can further enhance ALS disease progression.…”
Section: Immunometabolismmentioning
confidence: 99%
“…The dysregulation of the metabolic reprogramming process has been linked to a compromised immune system in patients with asthma [8][9][10]. The process of glycolysis which is the main source of energy in the body has been reported to be enhanced in patients with asthma [10].…”
Section: Introductionmentioning
confidence: 99%